2020
DOI: 10.1021/acscatal.0c02458
|View full text |Cite
|
Sign up to set email alerts
|

Surface Charge and Electrostatic Spin Crossover Effects in CoN4 Electrocatalysts

Abstract: Carbon materials doped with nitrogen and 3d transition metals have attracted a great deal of interest for catalyzing electrochemical reactions such as water splitting, oxygen reduction, and carbon dioxide reduction. Here, we employed density functional theory to study Co−N-doped carbon as electrocatalysts for the oxygen reduction and oxygen evolution reactions. Specifically, we investigated the interplay among adsorption energies, the spin state of the CoN 4 active center, and the applied potential. We found t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
93
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 104 publications
(99 citation statements)
references
References 46 publications
5
93
0
1
Order By: Relevance
“…This implies that the isolated Fe sites are the dominating active species for ORR 40 . The high ORR performance of Fe sites is related to their stronger bonding affinity of Fe centers toward O 2 molecules 41 , 42 , which is in line with previous literature 19 , 43 . To further elucidate the ORR process, Koutecky–Levich (K–L) equation and rotation ring-disk electrode (RRDE) tests were carried out.…”
Section: Resultssupporting
confidence: 90%
“…This implies that the isolated Fe sites are the dominating active species for ORR 40 . The high ORR performance of Fe sites is related to their stronger bonding affinity of Fe centers toward O 2 molecules 41 , 42 , which is in line with previous literature 19 , 43 . To further elucidate the ORR process, Koutecky–Levich (K–L) equation and rotation ring-disk electrode (RRDE) tests were carried out.…”
Section: Resultssupporting
confidence: 90%
“…In this case, the number of electrons transferred may deviate significantly from the number of H stripped/added. This effect has already been identified previously by theoretical studies considering constant-potential effects and it is used to explain pH-dependent electrocatalytic activity and selectivity, atomic structures of active sites, and electrostatic spin transitions in single-atom electrocatalyts, and so forth.…”
Section: Resultsmentioning
confidence: 67%
“…For example, Kim et al theoretically showed that the system charge significantly affects the activity of 2D electrocatalysts with atomic thickness . To this end, we also utilized the constant-potential method developed by Duan et al to explore the effects of U and pH values on the ORR activity of 2D biphenylene (see the Supporting Information for the computational details). As disclosed above, OOH* formation is the potential-limiting step, suggesting that the ORR activity of 2D biphenylene is actually governed by the adsorption free energy of OOH* species (Δ G OOH* ).…”
mentioning
confidence: 99%